PENINGKATAN STRATEGI HASIL BELAJAR IPA FISIKA PADA PROSES PEMBELAJARAN TEAM GATEWAY - Harefa, Darmawan (Unversitas Katolik Santo Thomas, 2020)
The purpose of this study was to determine the improvement of the science learning outcomes of physics at the Gateway Team learning process. The research method used was classroom action research (CAR) with a qualitative approach. Based on the results of the study found that the completeness of student learning in the first cycle of 55.17% still did not reach the target. In the second cycle, there was an increase with 100% student completeness which means that it had reached the target. Based on observations of teacher activities and student activities, obtained an increase in learning. To observe teacher activity increased from 72.12% in the first cycle to 94.23% in the second cycle. And for the observation of student activity increased from 72.73% in the first cycle to 90.91% in the second cycle. Then the research can be concluded that the application of Team Gateway learning strategies can improve student learning outcomes because it is very useful to support student creativity in analyzing problems to improve student learning outcomes. Researchers suggest teachers should use the Gateway Team learning strategy because students interact with one another to strengthen the knowledge they have acquired and also require students to work together in groups to solve problems in the material so that student learning outcomes are better and teachers are advised to use index cards and learning resources in the form of textbooks that are support student activities.